2001
DOI: 10.1097/00005344-200110000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Tolerability, and Impact on Quality of Life of Long-Term Treatment with Manidipine or Amlodipine in Patients with Essential Hypertension

Abstract: This double-blind, multicenter trial compared antihypertensive efficacy, tolerability, and impact on quality of life of manidipine and amlodipine in patients with mild-to-moderate essential hypertension. Patients were randomly assigned to 48 weeks of once-daily manidipine, 10-20 mg, or amlodipine, 5-10 mg. Patients who did not respond to treatment after 12 weeks were also given enalapril, 10-20 mg, for the study's duration. The main efficacy end point was equivalence in sitting systolic (SiSBP) and diastolic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Recent data have shown that not all dihydropyridine calcium antagonists are created equal with regard to vasodilatory edema. The third generation agents, such as lercanidipine and manidipine, have been shown to cause less edema than amlodipine [4,5]. Thus, despite lowering blood pressure to the same extent, the incidence of edema in patients on manidipine was only 8% compared with 21% in those on amlodipine (P < 0.0001) [4].…”
Section: Comparative Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data have shown that not all dihydropyridine calcium antagonists are created equal with regard to vasodilatory edema. The third generation agents, such as lercanidipine and manidipine, have been shown to cause less edema than amlodipine [4,5]. Thus, despite lowering blood pressure to the same extent, the incidence of edema in patients on manidipine was only 8% compared with 21% in those on amlodipine (P < 0.0001) [4].…”
Section: Comparative Findingsmentioning
confidence: 99%
“…The third generation agents, such as lercanidipine and manidipine, have been shown to cause less edema than amlodipine [4,5]. Thus, despite lowering blood pressure to the same extent, the incidence of edema in patients on manidipine was only 8% compared with 21% in those on amlodipine (P < 0.0001) [4]. Similarly, in a crossover study in patients who had side effects with other dihydropyridine calcium antagonists, the incidence of vasodilatory edema was significantly reduced when the patients were switched to lercanidipine at similar blood pressure levels [5].…”
Section: Comparative Findingsmentioning
confidence: 99%
“…However, when reported by patients as 'leg swelling', one of these thirdgeneration CCBs has been associated with an oedema incidence of 22%. 26 Thus, although differences among CCBs in oedema incidence rates have been reported in a number of studies, 10,[27][28][29][30] it is evident that dose-dependent peripheral oedema remains a common side effect in patients receiving both established and newer CCBs. 10,31 Factors that may influence oedema Several factors can predispose the patient to an increased risk of oedema.…”
Section: Mechanism Of Ccb-induced Oedemamentioning
confidence: 99%
“…3,4 With any form of edema, most physicians simply add a diuretic to the antihypertensive regimen. Unfortunately, diuretics have little effect on VDE.…”
mentioning
confidence: 99%